1763 Pa. Laws 306, An Act to prohibit the Selling of Guns, Gun-Powder, or other Warlike Stores, to the Indians, § 1 - (:unkn) unknown (My University, 1763)
Prohibited the giving, selling, bartering guns, ammunition, or warlike equipment to "any Indian," punishable by fine or imprisonment.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES